Adipose tissue dysfunction and visceral fat are associated with hepatic insulin resistance and severity of NASH even in lean individuals. (18th August 2022) - Saponaro, Chiara; Sabatini, Silvia; Gaggini, Melania; Carli, Fabrizia; Rosso, Chiara; Positano, Vincenzo; Armandi, Angelo; Caviglia, Gian Paolo; Faletti, Riccardo; Bugianesi, Elisabetta; Gastaldelli, Amalia
Abstract: Background & Aims: Non‐alcoholic fatty liver disease (NAFLD) is a heterogeneous disorder, but the factors that determine this heterogeneity remain poorly understood. Adipose tissue dysfunction is causally linked to NAFLD since it causes intrahepatic triglyceride (IHTG) accumulation through increased hepatic lipid flow, due to insulin resistance and pro‐inflammatory adipokines release. While many studies in NAFLD have looked at total adiposity (i.e. mainly subcutaneous fat, SC‐AT), it is still unclear the possible impact of visceral fat (VF). Thus, we investigated how VF versus SC‐AT was related to NAFLD severity in lean, overweight and obese individuals versus lean controls. Methods: Thirty‐two non‐diabetic NAFLD with liver biopsy (BMI 21.4–34.7 kg/m 2 ) and eight lean individuals (BMI 19.6–22.8 kg/m 2 ) were characterized for fat distribution (VF, SC‐AT and IHTG by magnetic resonance imaging), lipolysis and insulin resistance by tracer infusion, free fatty acids (FFAs) and triglyceride (TAG) concentration and composition (by mass spectrometry). Results: Intrahepatic triglyceride was positively associated with lipolysis, adipose tissue insulin resistance (Adipo‐IR), TAG concentrations, and increased saturated/unsaturated FFA ratio. Compared to controls VF was higher in NAFLD (including lean individuals), increased with fibrosis stage and associated with insulin resistance in liver, muscle and adipose tissue, increased lipolysis and decreased adiponectin levels. Collectively, our results suggest that VF accumulation, given its location close to the liver, is one of the major risk factors for NAFLD. Conclusions: These findings propose VF as an early indicator of NAFLD progression independently of BMI, which may allow for evidence‐based prevention and intervention strategies.